POTENTIALLY INAPPROPRIATE MEDICATION USE BY DEMENTIA FAMILY CAREGIVERS. (11th November 2018) - Yefimova, M; Pickering, C
Abstract: Psychotropic medication prescribing is common among community-dwelling older adults with dementia, even though it is associated with a significantly increased risk of mortality. Family caregivers have an impact on whether or not a medication is prescribed to their loved one with dementia, but less is known about how caregivers dispense the medications. This micro-longitudinal study examined medication dispensing practices by dementia family caregivers to describe potentially inappropriate medication use (PIM), in which the medication is intentionally used to sedate to make care easier rather than to manage a symptom. Caregivers (N=50) who live with their care-recipient completed online diaries for 21 days responding to questions on PIM and other daily contextual factors. Across 731 days, 11 caregivers (22%) reported PIM 82 times (11%). Daily contextual factors that significantly increased the odds of PIM included nighttime behavioral symptoms of dementia (OR = 6.5 [2.5–16.4]), no self-care activity (OR=4.0 [2.4–6.7]), and spending all 24 hours with the care recipient (OR=2.2 [1.3–3.8]). In a multi-level mixed model, the intraclass correlation coefficient revealed that 92% of variability in PIM use was accounted for by caregiver characteristics rather than daily contextual factors. Some caregivers did not report any PIM while others reported using it 19 out of 21 days. These findings indicate a possible type of caregivers who may be dispensing psychotropic medications as a coping strategy in the context of dementia care. Identifying high risk family caregivers and targeting their daily triggers is critical to reducing the effects of PIM among persons with dementia.